2016
DOI: 10.1242/dev.136259
|View full text |Cite
|
Sign up to set email alerts
|

Functional roles of MMP14 and MMP15 in early postnatal mammary gland development

Abstract: During late embryogenesis, mammary epithelial cells initiate migration programs that drive ductal invasion into the surrounding adipose-rich mesenchyme. Currently, branching morphogenesis is thought to depend on the mobilization of the membrane-anchored matrix metalloproteinases MMP14 (MT1-MMP) and MMP15 (MT2-MMP), which drive epithelial cell invasion by remodeling the extracellular matrix and triggering associated signaling cascades. However, the roles that these proteinases play during mammary gland developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 82 publications
1
53
0
Order By: Relevance
“…Likewise, we have found that the early phases of mammary gland branching morphogenesis occurring between embryonic day 16 and postnatal day 10 proceed independently of MT1-MMP (Feinberg et al, 2016). Largely unappreciated, however, neither the basement membrane nor the interstitial matrix of most organ systems are fully mature at birth or in the early postnatal period when the ECM is dominated by hyaluronic acid and associated proteoglycans (Loganathan et al, 2016).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Likewise, we have found that the early phases of mammary gland branching morphogenesis occurring between embryonic day 16 and postnatal day 10 proceed independently of MT1-MMP (Feinberg et al, 2016). Largely unappreciated, however, neither the basement membrane nor the interstitial matrix of most organ systems are fully mature at birth or in the early postnatal period when the ECM is dominated by hyaluronic acid and associated proteoglycans (Loganathan et al, 2016).…”
Section: Discussionmentioning
confidence: 82%
“…S1A-C). Recent studies have, however, demonstrated that mammary epithelial cells also express at least 2 members of the membrane-anchored MMP family, i.e., Mmp14/ MT1-MMP and Mmp15 /MT2-MMP (Feinberg et al, 2016). Indeed, using Mmp14 +/LacZ and Mmp15 +/LacZ knock-in lines, both MT-MMPs are readily detected during morphogenesis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second phase, cell death is accompanied by upregulation of matrix metalloproteinases (MMPs) which are important in the remodeling of the surrounding stroma, accompanied by adipocyte refilling, influx of macrophages, and active plasma kallikrein formation that regulates adipocyte differentiation and stromal remodeling [51]. The MMPs such as MMP14 and MMP15 regulate adipocyte differentiation with promoting deposition of white fat and brown fat, respectively [52]. Circulating factors regulate this phase and it is observed systemic administration of glucocorticoids [6,53] halts this phase which may act through the maintenance of tight junctions [54].…”
Section: Mammary Gland During Involutionmentioning
confidence: 99%